Vascular Parkinsonism with Severe Gait Disturbance: A Case Report - Ahmad Dalma Haidar; Arda Fatkhul Khoiriyah (The Indonesian Journal of General Medicine, 2026)
Introduction: Vascular parkinsonism (VP) is a secondary parkinsonian syndrome caused by cerebrovascular lesions affecting the basal ganglia, subcortical white matter, or nigrostriatal pathways. It commonly affects elderly patients with vascular risk factors and is often misdiagnosed as idiopathic Parkinson's disease (PD). This case report aims to describe the clinical, radiological, and therapeutic features of a patient with severe gait-dominant VP. Case Illustration: A 72-year-old male with a 15-year history of hypertension, 10-year history of type 2 diabetes mellitus, dyslipidemia, and a prior ischemic stroke presented with a one-year history of progressive gait difficulty that severely worsened over the last two months. Clinical examination revealed short-step gait, freezing of gait, start hesitation, postural instability, bilateral lower limb lead-pipe rigidity, bradykinesia, minimal resting tremor, hyperreflexia, and bilateral Babinski signs. Brain CT showed extensive leukoaraiosis in periventricular and deep white matter, cerebral atrophy, and chronic small vessel ischemic disease. The patient received levodopa/carbidopa 100/25 mg three times daily, aspirin, atorvastatin, amlodipine, metformin, and intensive physiotherapy. After 10 days of hospitalization, only minimal improvement was observed, with persistent gait dependency and poor levodopa response. Discussion: VP is characterized by lower body parkinsonism, poor response to levodopa, and upper motor neuron signs. Neuroimaging plays a key role in distinguishing VP from PD. Management focuses on vascular risk factor control and rehabilitation. Conclusion: VP should be suspected in elderly patients with vascular risk factors, predominant gait disturbance, and poor levodopa response. Early diagnosis and secondary prevention are essential.